PkM Kopontren Daarul Rahman Cipedak Jagakarsa Jakarta Selatan melalui Kewirausahaan Syariah berbasis Smartphone - Yunika Murdayanti; Susi Indriani (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2019)
The existence of Pesantren Cooperation can be viewed through three dimensions, such as a supporter of the economic life mechanism of Pesantren (Islamic Institution), as a coaching cadre of rural cooperation and as a socio-economic stimulator of rural communities around boarding school. However, there is a problem, the lack of access to knowledge and entrepreneurship education programs for students will raise worries of intellectual understanding and the increase of their soft skills. The method of implementing this service is carried out at the cooperation of Pesantren Daarul Rahman in South Jakarta through interviews, lectures on training material, practices and discussions on inventory and financial training using information technology applications both with Ms. Excell computer programs and smartphone-based digital applications. Achieving the results of this activity is an increase in the ability of managerial skills and have the ability to use information technology in its application to digital financial records.